(untitled) (New York, 2006)
The bestselling textbook inorganic chemistry text on the market covers both theoretical and descriptive aspects of the subject, and emphasizes experimental methods, industrial applications, and modern topics.
Anh Văn chuyên ngành Sư phạm Hóa,Hóa vô cơ 1,Hóa vô cơ 2
Keywords: Chemistry, Inorganic,Hóa học vô cơ; Textbooks,Sách giáo khoa